Notes on unequal exchange between developing and industrialised countries - Detlef Lorenz (Intereconomics, 1982)
Proponents of the theory of unequal exchange claim that the international division of labour is based on the exploitation of the developing countries by the industrialised countries. But the international division of labour allows the developing countries to import goods which they either could not produce themselves, or only at a higher price than they pay for the imports. The lower wage-levels in the developing countries may also help them to obtain employment at the expense of the industrialised countries. Low wages are therefore ultimately not a question of exploitation but of development priorities.
Keywords: 330; International Trade